"The flu… is a little more complicated than a cold": Knowledge, beliefs, and practices related to influenza and influenza vaccination among at-risk populations and health professionals in Peru. Issue 48 (10th November 2020) - Garcia, Patricia J.; George, Paul E.; Romero, Candice; Soto, Giselle; Carcamo, Cesar; Bayer, Angela M.
Highlights: Health professional and at risk community member participants underestimated influenza prevalence. Both also correctly identified major influenza-associated symptoms. Providers missed opportunities to vaccinate and overestimated vaccine side-effects. Community members had low knowledge about the influenza vaccine. Text-messaging was identified as a possible way of disseminating information. Abstract: Background: Influenza is a major source of morbidity and mortality with an annual global attack rate estimated at 5–10% in adults and 20–30% in children. Influenza vaccination is the main strategy for reducing influenza-related morbidity and mortality. Like several other countries, Peru has low vaccination coverage, estimated at 25–50% among young children and older adults. Therefore, the study objective was to explore the knowledge, beliefs, attitudes, and practices related to influenza vaccination among populations at higher risk for infection and/or complications and health professionals in Peru, and their perspectives on health communication channels. Methods: This qualitative study was carried out in three cities. We held nine focus groups with pregnant and postpartum women, parents of young children, and older adults. We carried out 25 in-depth interviews with health professionals (HPs) working in, leading or advising immunization-related programs. Results: HPs correctly identified the causes of influenza and HPs and at risk community members identified major symptoms. Community members had poor awareness of the potential severity of influenza and were generally unaware of influenza-related mortality. Both HPs and community members greatly underestimated the prevalence of influenza in Peru. HPs in our study overestimated major side effects of the influenza vaccine and community members perceived that the vaccine caused illness. HPs missed important opportunities to promote vaccination in patients with minor illness (runny nose, allergies, colds) and community members did not understand that the vaccine should be received annually. Conclusions: There is no single strategy that will increase influenza vaccination rates to World Health Organization recommended levels. Instead, it requires multi-faceted commitment from HPs, other healthcare authorities and the government. Addressing important knowledge barriers, specifically negative views regarding the influenza vaccine and the severe morbidity and mortality associated with influenza illness, both in the community and especially among HPs, could have significant impacts.